Expression profile of salivary micro RNA-21 and 31 in oral potentially malignant disorders - Thirupambaram Natarajasundaram UMA MAHESWARI; Malli Sureshbabu NIVEDHITHA; Prathiba RAMANI (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Oral potentially malignant disorders (OPMD) possess significant chances of malignancy conversion. In order to develop an early diagnostic tool, the present study evaluated the expression of miRNA-21 and 31 as salivary markers. The case-control study was carried out in 36 healthy participants as controls and in 36 patients who were newly diagnosed as OPMD having four different lesions including leucoplakia, oral sub mucous fibrosis (OSMF)궱, oral lichen planus, and (OSMF)궱 with leucoplakia. The samples were also classified as non-dysplastic, or with mild, moderate, and severe dysplasia according to their histopathological reports. The salivary miRNA-21 and 31 expressions were studied using real-time PCR. The statistical analysis was carried out using SPSS version 22. Salivary miRNA-21 (p-value = 0.02) and 31 (p-value = 0.01) were significantly upregulated in severe dysplasia compared with control. Among the different lesions, leucoplakia had significant upregulation of miRNA-21 and 31. miRNA-21 can be used as a diagnostic marker with specificity of 66% and sensitivity of 69%. The area under the ROC curve was 0.820 for miRNA-21 and 0.5 for miRNA-31, which proved that miRNA-21 is a better diagnostic marker than miRNA-31 for OPMD.